Interpersonal Forgiveness as an Example of Loving One'S Enemies - Worthington, Everett L. (Journal of psychology and theology, 2006)
We suggest that altruistically-motivated forgiveness is an ideal we rarely achieve. In fact, we often think such forgiveness is impossible. Our contribution is to identify ways that God promotes forgiveness—specifically the ideal forgiveness that demonstrates altruistic love for our enemies. We see God at work in the human psychological processes of forgiving with altruistic motives. We thus address four questions: (1) How do motives shape forgiveness? (2) How do virtues shape forgiveness? (3) How are motives transformed? (4) How do Scripture and God contribute to transforming motivations from justice-oriented motives to forgiveness-oriented motives? Compared with previous writings on forgiveness, we focus more on how transformations of motives and emotions occur.